The weakness of God: a theology of the event - Caputo, John D. (Indiana series in the philosophy of religion, 2006)
Applying an ever more radical hermeneutics (including Husserlian and Heideggerian phenomenology, Derridian deconstruction, and feminism), John D. Caputo breaks down the name of God in this irrepressible book. Instead of looking at God as merely a name, Caputo views it as an event, or what the name conjures or promises in the future. For Caputo, the event exposes God as weak, unstable, and barely functional. While this view of God flies in the face of most religions and philosophies, it also puts up a serious challenge to fundamental tenets of theology and ontology. Along the way, Caputo's read